PERSEPSI MAHASISWA TENTANG PEMILIHAN TEMPAT KERJA - Mardeyanti Mardeyanti Mardeyanti; Fatimah Fatimah Fatimah; Aisyah Aisyah Aisyah (Jurnal Ilmu dan Teknologi Kesehatan, 2015)
One important effort that has been implemented by the Government of Indonesia to accelerate the reduction of MMR (Maternal Mortality Rate) and IMR (InfantMortality Rate) in Indonesia is narrowing the distance between health care services and community. Midwife graduates in choosing a job is influenced by the readiness of the knowledge and skills. Study aimed to investigate the perception of the relationship with the midwife profession workplace elections. This study uses survey research design cross sectional analytic approach. The respondents were Graduate Diploma of Midwifery a number of 115 people. Study results showed 59.1 % have a good perception, but only 21.7 % students who chose to work in the rural . Another variable results showed 51 % students motivation , 63.5 % with interest in accordance with the profession , 82.6 % expect an increase in financial , 74.8 % with good family support , and 93% expect an increase in career . The results of the bivariate analysis there was no significant association with the perception of the election work in the rural with a p value of 0.43 . The variables that most influence on the workplace is a career path variable ( B = 1.007 ). Good perception does not make students have a desire to work in the rural. Improvement of career path is the reason for choosing to work in the city.